ZIF-67 derived Co3S4 hollow microspheres and WS2 nanorods as a hybrid electrode material for flexible 2V solid-state supercapacitor. (10th June 2020) - Shrivastav, Vishal; Sundriyal, Shashank; Goel, Priyanshu; Shrivastav, Vaishali; Tiwari, Umesh K.; Deep, Akash
Abstract: Transition metal dichalcogenides (TMDs) are gaining interest in the energy sector due to its 2D chemistry and heterogeneous characteristics however its stability for the long run and poor electrical conductivity are pushing the researchers to make their hybrid. Herein we synthesized the hybrid WS2 nanorods and Co3 S4 microspheres composite material which attained a high energy density of 47.3 Wh/kg along at a high-power density of 512 W/kg. The hollow Co3 S4 microspheres were synthesized using highly porous ZIF-67 as a precursor. Furthermore, these hollow Co3 S4 microspheres are in-situ modified by combining with WS2 nanostructures to enhance its energy density. The electrodes with the synthesized hybrid material deliver the specific capacitance of 412.7 F/g at the current density of 1 A/g, Additionally, two equal weighted Co3 S4 /WS2 composite electrodes are used to fabricate an all-solid-state symmetrical supercapacitor device with PVA-1M H2 SO4 polymer gel electrolyte, exhibiting a wide potential window of 2 V with 92% cyclic stability (2000 charge-discharge cycles) demonstrates its potential applicability for the supercapacitor application. The excellent electrochemical performance and splendid cyclic stability are attributed to the synergy of high surface area ZIF-67 derived Co3 S4 microsphere for fast charge transfer with 2D networked WS2 material responsible to provide high energy density. Graphical abstract: Image 1 Highlights: A hybrid Co3 S4 /WS2 composite was prepared using a one-step solvothermal method. The hybrid composites deliver the highest specific capacitance of 412.7 F/g at the current density of 1 A/g. A solid-state symmetrical supercapacitor was assembled with PVA-1M H2 SO4 gel electrolyte as a separator. With wide potential window of 2 V, the fabricated device attained a high energy density of 47.3 Wh/kg along at a high-power density of 512 W/kg.